Do the Fertility Drugs Increase the Risk of Cancer? A Review Study - Momenimovahed, Zohre; Taheri, Safoura; Tiznobaik, Azita; Salehiniya, Hamid (Frontiers in Endocrinology, 2019)
Aim: All over the world, many couples are not able to get pregnant. Ovulation-inducing drugs are among the most important drugs used for the treatment of infertility. In recent years, there has been many debates about the relationship between fertility medication and cancer. Since knowing the relationship between the use of fertility drugs and cancer is important and due to the lack of comprehensive study in this regard, the present study was conducted to investigate the relationship between infertility drugs and cancer among women. Materials and methods: To determine the relationship between infertility treatment and cancer, a comprehensive search was carried out in Medline, Web of Science Core Collection, and Scopus from their inception, using the following keywords: "Infertility", "ovulation induction", "cancer", "infertility treatment". Full-text, English language and original articles with keywords in the title, abstract or keywords were included in this study. Results: In total, 50 articles were entered into the study. Relationship between fertility medications and breast, ovary, endometrial, uterus, colon, thyroid, skin, cervical and Non-Hodgkin's lymphoma cancer were studied. Although relationship between fertility medications and cancer are theoretically justifiable, most studies have shown no increased risk of cancer after fertility treatment. Conclusion: The results of this study did not find any established evidence that fertility medications affect the risk of cancer among users. In conclusion, the relationship between infertility treatment and cancer incidence remains an open question.